Microparticles based on chitosan/carboxymethylcellulose polyelectrolyte complexes for colon delivery of vancomycin. (5th June 2016) - Cerchiara, T.; Abruzzo, A.; Parolin, C.; Vitali, B.; Bigucci, F.; Gallucci, M.C.; Nicoletta, F.P.; Luppi, B.
Highlights: Polyelectrolyte complexes were prepared for colon-specific delivery of vancomycin. Polyelectrolyte complexes were based on chitosan (CH) and carboxymethylcellulose (CMC). Particles were prepared by spray-drying process. The best formulation was CH/CMC 1:3. Abstract: The aim of this work was to prepare polyelectrolyte complexes based on chitosan (CH) and carboxymethylcellulose (CMC) for colon delivery of vancomycin (VM). Various batches of polyelectrolyte complexes, using three different CH/CMC weight ratios (3:1, 1:1 and 1:3), were prepared and collected as microparticles by spray-drying process. Microparticles were characterized in terms of yield, encapsulation efficiency, drug loading, morphology and mucoadhesion properties. Microparticles water-uptake and VM release as well as its protection against gastric pepsin degradation were also investigated. Finally, the antibacterial activity against Staphylococcus aureus, a Gram-positive model strain, was evaluated. The best formulation CH/CMC 1:3 was selected based on the encapsulation efficiency, water-uptake and drug release rate. Moreover, microparticles were able to prevent VM degradation and showed a good antibacterial activity against S. aureus. Finally, to improve the release of VM in the colon the selected formulation was coated with lauric acid.